Systematic analysis of lysine malonylation in Streptococcus mutans - Li, Zhengyi; Wu, Qinrui; Zhang, Yixin; Zhou, Xuedong; Peng, Xian (Frontiers in Cellular and Infection Microbiology, 2022)
Protein lysine malonylation (Kmal) is a novel post-translational modification (PTM) that regulates various biological pathways such as energy metabolism and translation. Malonylation in prokaryotes, however, is still poorly understood. In this study, we performed a global Kmal analysis of the cariogenic organism Streptococcus mutans by combining antibody-based affinity enrichment and high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) analysis. Altogether, 392 malonyllysine sites in 159 proteins were identified. Subsequent bioinformatic analysis revealed that Kmal occurs in proteins involved in various metabolic pathways including translation machinery, energy metabolism, RNA degradation, and biosynthesis of various secondary metabolites. Quantitative analysis demonstrated that Kmal substrates were globally altered in the biofilm growth state compared to the planktonic growth state. Furthermore, a comparative analysis of the lysine malonylome of our study with previously determined lysine acetylome in S. mutans revealed that a small proportion of Kmal sites overlapped with acetylated sites, whereby suggesting that these two acylations have distinct functional implications. These results expand our knowledge of Kmal in prokaryotes, providing a resource for researching metabolic regulation of bacterial virulence and physiological functions by PTM.